Acute localised exanthematous pustulosis (ALEP) induced by clindamycin in pregnancy. (14th January 2014) - De Cruz, Ryan; Ferguson, John; Wee, Jamie S; Akhras, Victoria
Abstract Acute generalised exanthematous pustulosis (AGEP) or toxic pustuloderma (TP) is an uncommon though well‐recognised cutaneous hypersensitivity reaction that is usually drug‐induced. It presents with a triad of scattered sterile pustules, fever and malaise. Acute localised exanthematous pustulosis (ALEP) is a rare and unusual variant of AGEP. We describe a case of ALEP triggered by oral clindamycin that occurred during pregnancy.